KOMPOSISI KIMIA BIJI DAN SIFAT FUNGSIONAL PATI GAYAM (Inocarpus edulis Forst.) 1) [Chemical Composition of Gayam ( Inocarpus edulis Forst.) Seed and Functional Properties of Its Starch] - Indah Epriliati; Purwiyatno Hariyadi; Anton Apriyantono (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2002)
Basic information on physical and chemical properties of Gayam (Inocarpus edulis Forst), one of the domestic commodities, is still very limited. The objectives of this research were to investigate chemical composition of gayam seed and the functional properties of gayam starch, especially the pasting behavior and the characteristic of its gel. Moisture, crude protein, lipid, ash, and carbohydrate content of gayam seed, respectively, were 50.11% (w/w), 11.66%, 8.21 %, 3.39% , and 76.74% (dw). The gayam starch granules were very strong and remain physically intact during heating up to 90°C. The highest swelling-power (24.76) occurred at 95°C, with low amylose leaching (0.27% dw) and solubility (0.25° Brix). Pasting behavior of starch suspension (10% w/v) showed the initial pasting temperature at 81°C and peak viscosity 750 Brabender unit (BU) reached at 90 °C. The paste viscosity was relatively stable at 95°C. The gel was formed during cooling. The gel of gayam starch was unstable at (-16°C) at which six times freezing-thawing cycles resulted in 66.95% water dripped. The gel characteristics may indicated the high amylose content. Scanning electron micrographs of freeze-dried gel revealed the sponge-strucuture. The data indicated that gayam starch has great potential to be explored further for industrial applications.